Effect of polyphenol-rich oil palm empty fruit bunch extract on in vitro rumen fermentation, fatty acid profile and microbial population - Harun, Nur Liyana Akmal; Samsudin, Anjas Asmara; Sazili, Awis Qurni; Goh, Yong Meng (Czech Academy of Agricultural Sciences, 2025)
The aim of this study was to evaluate the effect of oil palm empty fruit bunch (OPEFB) extract on in vitro rumen fermentation, fatty acid profile, and microbial population. Rumen fluid was obtained from three female dairy goats fed a similar diet of 60% Napier grass and 40% commercial pellets. The substrate used for the fermentation was a Napier grass and commercial pellet mixture (60: 40 in dry matter) and the treatment diets were: CON (substrate without OPEFB extract), OPEFB-5 (substrate with 5% of OPEFB extract), OPEFB-10 (substrate with 10% of OPEFB extract). The characteristics of rumen fermentation including pH, fermentation kinetics, total gas production, volatile fatty acid (VFA) production, fatty acid (FA) production, and microbial populations were examined. Results showed that OPEFB supplementation decreased rumen acetate concentration, increased isoacid concentrations as well as palmitic acid concentration. Meanwhile, the population of total bacteria, protozoa, and B. fibrisolvens decreased with the OPEFB supplementation. OPEFB-5 resulted in a moderate amount of acetate, isobutyrate, isovalerate concentration, insoluble fraction of gas production (but degradable), estimated potential gas production as well as B. fibrisolvens population when compared with the control and OPEFB-10 diet. Therefore it is suggested that the supplementation of OPEFB extract at 5% is suitable and practical to be used in ruminant feed without causing an imperative effect on rumen fermentation.